Toward an experimental account of argumentation: the case of the slippery slope and the ad hominem arguments - Lillo-Unglaube, Marco; Canales-Johnson, Andrés; Navarrete, Gorka; Bravo, Claudio Fuentes (Frontiers in Psychology, 2014)
Argumentation is a crucial component of our lives. Although in the absence of rational debate our legal, political, and scientific systems would not be possible, there is still no integrated area of research on the psychology of argumentation. Furthermore, classical theories of argumentation are normative (i.e. the acceptability of an argument is determined by a set of norms or logical rules), which sometimes creates a dissociation between the theories and people’s behavior. We think the current challenge for psychology is to bring together the cognitive and normative accounts of argumentation. In this Perspective, we exemplify this point by analyzing two cases of argumentative structures experimentally studied in the context of cognitive psychology. Specifically, we focus on the slippery slope argument and the ad hominem argument under the frameworks of Bayesian and pragma-dialectics approaches, respectively. We think employing more descriptive and experimental accounts of argumentation would help Psychology to bring closer the cognitive and normative accounts of argumentation with the final goal of establishing an integrated area of research on the psychology of argumentation.